Trends and New Challenges in the Green Supply Chain: The Reverse Logistics - José Antonio Plaza-Úbeda (Sustainability, 2021)
As members of society, companies are exposed to social changes and pressures. Hence, an interest to be more environmentally friendly appears and rises in their core. Therefore, the supply chain management concept became "greener" with the development, among other practices, of reverse logistics programs. Both external pressures and internal factors, such as reducing costs and increasing operational performance, are motivating companies to pay more attention to the reverse flow. Unfortunately, there are still many boundaries that hinder the implementation of reverse logistics. Some of these obstacles include additional costs, the desire for deep collaboration with suppliers and customers, and the belief of some managers that are managing reverse flow that it is not worth the trouble. On the contrary, those who have assimilated its importance and advantages are interested in new and innovative tools that could contribute to more effective and efficient results, including the role of RFID technology.